2015
DOI: 10.1021/acs.energyfuels.5b01842
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Effects of Air Jet Pressure and Temperature on High-Pressure Air Jet Controlled Compression Ignition Combustion Based on a Novel Thermodynamic Cycle

Abstract: To control premixed charge compression ignition (PCCI) phasing in internal combustion engines, a novel method called high-pressure air jet controlled compression ignition (JCCI) based on compound thermodynamic cycle was proposed to achieve diesel premixed combustion in all load operations. The method is implemented in a hybrid pneumatic engine (HPE). The application of HPE is also beneficial to the fuel consumption and emissions because of its several flexible operation modes. The purpose of this paper is to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In order to effectively control the combustion in the PCCI mode, jet controlled compression ignition (JCCI) combustion mode was proposed. 3133 High-pressure air (HPA) JCCI combustion is accomplished in HPE based on the compound thermodynamic cycle. It uses the high-pressure air jet compression to trigger the auto-ignition, and the combustion process can be controlled flexibly by the air jet conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to effectively control the combustion in the PCCI mode, jet controlled compression ignition (JCCI) combustion mode was proposed. 3133 High-pressure air (HPA) JCCI combustion is accomplished in HPE based on the compound thermodynamic cycle. It uses the high-pressure air jet compression to trigger the auto-ignition, and the combustion process can be controlled flexibly by the air jet conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It uses the high-pressure air jet compression to trigger the auto-ignition, and the combustion process can be controlled flexibly by the air jet conditions. 32,34 The previous work showed that HPA JCCI characterizes the intensified low-temperature reaction and two-stage high-temperature reaction. A higher air jet temperature leads to a higher peak pressure, a shorter combustion duration and a higher combustion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In JCCI combustion mode, the ignition of premixed charge in cylinder is triggered directly by the jet. The jet could be a high temperature jet issued from a pre-chamber or high-pressure air jet or even diesel fuel jet [21][22][23][24]. In the thermal and chemical effects of the jet, the in-cylinder lean mixture ignites spontaneously.…”
Section: Introductionmentioning
confidence: 99%